2020
DOI: 10.1101/2020.09.20.20197608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

At home and online during the early months of the COVID-19 pandemic and the relationship to alcohol consumption in a national sample of U.S. adults

Abstract: Objective: The current study seeks to understand the links between social media use and alcohol consumption during the early months of the COVID-19 pandemic. Method: Data were from the national Understanding American Study, a probability-based Internet panel weighted to represent the U.S. population. Subjects (N=5874; 51% female) were adults, 18 years and older, who completed a March survey (wave 1) and a follow-up survey one month later (wave 3). Analyses assessed the relationship of social media use at wave … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A study conducted during June 2020 found that college students had excessive use of social networking sites and lack of personal control to disengage themselves from those sites [ 42 ]; this tendency was also associated with the use of alcohol, tobacco, cannabis, and sedative without a doctor’s prescription. Another study conducted in March and April 2020 in the U.S. suggested that exposure to COVID-19 information, via Twitter, Instagram, and Facebook, and increased alcohol use in March contributed to more frequent alcohol consumption in April, especially those working or studying from home [ 43 ]. These empirical studies suggest that even though ICT provides a means of social connection with one’s social networks and the wider community, moderate and responsible use is important in maintaining a healthy approach to it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted during June 2020 found that college students had excessive use of social networking sites and lack of personal control to disengage themselves from those sites [ 42 ]; this tendency was also associated with the use of alcohol, tobacco, cannabis, and sedative without a doctor’s prescription. Another study conducted in March and April 2020 in the U.S. suggested that exposure to COVID-19 information, via Twitter, Instagram, and Facebook, and increased alcohol use in March contributed to more frequent alcohol consumption in April, especially those working or studying from home [ 43 ]. These empirical studies suggest that even though ICT provides a means of social connection with one’s social networks and the wider community, moderate and responsible use is important in maintaining a healthy approach to it.…”
Section: Literature Reviewmentioning
confidence: 99%